EFFECT OF CONCENTRATION AND SOAKING TIME ON LIQUID SMOKED SOLVENT OF SAGO BARK TO THE MICROBIOLOGY QUALITY OF SMOKED CATFISH (Pangasius hypophthalmus) FILLET - Febrina M Febrina; Syahrul Syahrul; N.Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was aimed to determine the exact concentration and soaking time on liquid smoked solvent of sago bark to the microbiology quality.The experimental method was used in this research with factorial Completely Randomized Design. The first factor was the concentration of liquid smoked solvent with 3 treatment levels K1 (5%), K2 (7%) and K3 (9%), the second factor was soaking time on liquid smoked solvent with 3 treatment levels L0 (0 minute), L1 (60 minutes) and L2 (120 minutes). The tested parameters were microbiology analysis (total  bacterial colony, Staphylococcus aureus, Salmonella sp, Escherichia coli) and organoleptik analysis (appearance, odor, taste and texture). The result showed that the smoked catfish fillet was significantly affect to the microbiology and organoleptik quality. Whereas the treatment with 9% of liquid smoked solvent and 120 minutes of soaking time (K3L2) was the best treatment with total bacterial colony 2.43 x 103colony/g, Staphylococcus aureus 0.73 x102colony/g, Salmonella sp (negatif), Escherichia coli<3 AMP/g, and organoleptik appearance K3L1with characteristics of  clean and shiny brown color (7.13),a distinctive of smoked odor(7.88) and taste (7.32),and a compact texture (7.35).